HAK INDIVIDU, KEPENTINGAN PUBLIK, DAN REPRESI TOLERAN: STUDI KASUS JALUR TRUK SRUMBUNG MAGELANG DALAM PERSPEKTIF TEORI HERBERT MARCUSE - Sudrajat; Victor Novianto; Choirun Nisaa (Jurnal Sosialita, 2026)
The use of alternative routes by truck drivers in Srumbung, Magelang, raises ethical and social questions regarding the boundaries between individual freedom and collective responsibility. This study aims to analyze such actions through Herbert Marcuse’s theory of repressive tolerance and employs a critical qualitative approach grounded in four analytical principles: (1) true freedom involves awareness of social impact; (2) unreflective freedom reinforces structural domination; (3) personal actions must consider social justice; and (4) individual rights are limited by collective rights. These four principles serve as analytical tools to examine the phenomenon of logistical system domination over rural community spaces. The findings reveal that individual actions perceived as free actually operate within constructed power structures and the pressures of capitalist efficiency. Such actions tend to ignore broader social structures and reinforce existing inequalities. This article emphasizes the importance of critical reflection on personal choices to uphold social justice in shared spaces.